Local variations in grain formation, grain boundary sliding, and whisker growth along grain boundaries in large-grain Sn films. (October 2020) - Chen, Wei-Hsun; Wang, Congying; Sarobol, Pylin; Blendell, John; Handwerker, Carol
Abstract: Two grain boundaries (GBs) in a Sn-alloy film exhibited different morphological changes during thermal cycling: whisker growth and GB sliding. Along GB-I, pervasive nucleation of high-angle and low-angle GBs occurred, with whisker growth of some shallow grains depending on sub-surface GB geometry. Most whiskers showed substantial changes of crystallographic orientation and surface normal relative to the parent grains. Along GB-II, GB sliding was characterized by mass accumulation, crystallographic rotation, and localized yielding. Results for two GBs suggest that grain crystallography and GB geometry, particularly GB inclination, are critical in determining the extent of new grain formation and subsequent whisker growth. Graphical abstract: Image, graphical abstract